Faktor Yang Mempengaruhi Income Smoothing Pada Perusahaan Manufaktur Di BEI Tahun 2013-2015 - Rini Tri Hastuti (Jurnal Ekonomi, 2017)
The purpose of this research is to reexamine the factors that allegedly affect income smoothing, whiches firm size, profitability, financial leverage, institutional ownership. The sample of this study consisted of 59 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2013 until 2015. To determine the status of the grading company and not a profit grader used the Eckel index. As for answering the research hypothesis used Logistic Regression analysis tools. The results of this study conclude that income smoothing taken by the company to go public in the Indonesia Stock Exchange (IDX). Multivariate testing using the Logistic Regression showed that firm size, profitability, financial leverage has a significant effect on income smoothing. While the variable institutional ownership had no significant effect on income smoothing.